INHIBITION OF Escherichia coli O157:H7 CONTAMINATION ON CHICKEN MEAT BY NATURAL VINEGAR PREPARED FROM BANANA PEEL AND COCONUT WATER - Miskiyah, M.; Juniawati, J.; Andriani, A. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
The use of vinegar as a natural preservative to inactivate microbial growth in meat was investigated. Vinegar was prepared from banana peel and coconut water, and the efficacy against Escherichia coli O157:H7 was tested. Chicken meat were treated with vinegar solution (equals to 1% acetic acid), acetic acid solutions (1%), and lactic acid solutions (2%), control (distilled water). Samples were soaked with acid solution treatment for 1 minute (1.125:1 w/v; chicken meat: solution treatment). Treated samples were inoculated with E. coli O157:H7 on the surface of the chicken meat, then left for 20 minutes for absorption of bacteria into the meat. Observation was done at 0, 3, 6, 9, and 12 days at low temperature storage, and at 0, 6, 12, 18, 24 hours at room temperature storage. The results showed that banana peel vinegar and coconut water vinegar were effective as natural preservative. In conclusion, the vinegar were potentially inhibited E. coli O157:H7 growth at chicken meat until 12 hours at room temperature storage and 9 days at cold temperatures.